Evaluation of the Scout Extracurricular Program at SMP Negeri 1 Percut Sei Tuan - Rahmad Rinaldi, Askur Amin, M. Syahputra BB (LPPPI Publishing, 2021)
The purpose of this paper is to discuss the evaluation of the Scout extracurricular program at SMP Negeri 1 Percut Sei Tuan, this research method uses an evaluative research design with a descriptive-quantitative approach, the results of this study are: have values or norms for the appreciation of noble character, the input is good because students go through the selection of junior high school entrance tests and the coaches already have a KMD diploma, the process is good, because all scouting activities or work programs can be carried out well, as evidenced by many the achievements achieved by SMPN Megang Sakti. If viewed from the product, SMPN students often achieve achievements, but in groups, if individually, SMPN students still lack the level of religiosity, skills, communication and social arts. But very good at independence, discipline, manners and a strong personality.